Characterisation of hyaluronidase, biofilm formation and emm type among invasive and non-invasive Streptococcus pyogenes clinical isolates in two hospitals in Malaysia - Wan Mansor, Wan Muhammad Zamir (2019)
Streptococcus pyogenes or group A streptococcus (GAS) is one type of bacterium that causes a wide variety of infectious and immunologically-related diseases. Hyaluronidase enzyme produced by GAS degrades hyaluronic acid, a major component in extracellular matrix of human connective tissues allowing the pathogen to enter. Meanwhile, biofilm formation in GAS is associated with therapeutic failure due to the robustness of biofilms against antibiotics. Till date, little is known on GAS hyaluronidase, its gene (Hyl) and biofilms. The aims of this study were to determine the production of bacterial hyaluronidase and its molecular characteristics and biofilm formation as well as emm typing among GAS clinical isolates. A total of 45 S. pyogenes clinical isolates were obtained from the previous stock cultures which were collected from Kuala Lumpur and Serdang hospitals. Phenotypic hyaluronidase production was assessed by a solid plate assay. Hyl genes (HylA, HylP1, HylP2, HylP3) were detected through multiplex PCR using established primers. emm typing was done by emm gene amplification and sequencing according to established protocols. The enzymatic activity of hyaluronidase from different GAS isolates was determined through hyaluronic acid turbidity reduction assay. Biofilm formation was detected using Congo Red Agar (CRA) and Crystal Violet Assay (CVA). Forty isolates (88.9%) exhibited hyaluronidase production despite the presence of Hyl genes (chromosomal and phage-associated) in all isolates. Hyaluronidase exhibited the maximum activity at 10th minute time point with appropriate conditions that include 3% of bovine serum albumin (BSA), pH 3.5 and 0.1M NaCl. Positive correlation between bacterial growth and enzymatic activity was observed (p value < 0.05). Most of the strains exhibited moderate biofilm production, (30, 66.66%) in CRA and (23, 51.11%) in CVA. A total of 29 different emm types were detected. The most prevalent emm types were emm1, 18, 28, 97 and 102 with (6.7%) of the isolates each, while emm types 63, 71, 76, 89 and 91 were seen in 4.4% of the isolates respectively. The rest of the emm types 12, 15, 44, 56, 65, 81, 98, 101, 105 and 120 were found about 2.2% each. No new emm types were detected. In general, there was no strong association between hyaluronidase production, emm type, invasiveness and biofilm formation as p values were more than 0.05). Hyaluronidase and production of biofilms in GAS may be involved in its pathogenesis as hyaluronidase able to break hyaluronic acid (HA) which is the layer wall on the host cells and the development of biofilm aid bacteria to become antimicrobial resistance towards antibiotics. Diverse emm types in the study may signify the heterogeneity of the local GAS strains. More research is warranted in future to establish to link between GAS virulence factors and its biofilms.